2018
DOI: 10.1038/s12276-018-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronary stents with inducible VEGF/HGF-secreting UCB-MSCs reduced restenosis and increased re-endothelialization in a swine model

Abstract: Atherosclerotic plaques within the vasculature may eventually lead to heart failure. Currently, cardiac stenting is the most effective and least invasive approach to treat this disease. However, in-stent restenosis is a complex chronic side effect of stenting treatment. This study used coronary stents coated with stem cells secreting angiogenic growth factors via an inducible genome-editing system to reduce stent restenosis and induce re-endothelialization within the artery. The characteristics of the cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The current research in this field mainly focuses on improving the function of VSMcs (14)(15)(16)(17)21); however, Ecs have not been extensively investigated. The delay in endothelialization severely compromises the therapeutic effect of Ecs (40). Previously published data by the authors of the current study demonstrated that miR-24 was enriched in VSMcs rather than Ecs (41).…”
Section: Discussionmentioning
confidence: 54%
“…The current research in this field mainly focuses on improving the function of VSMcs (14)(15)(16)(17)21); however, Ecs have not been extensively investigated. The delay in endothelialization severely compromises the therapeutic effect of Ecs (40). Previously published data by the authors of the current study demonstrated that miR-24 was enriched in VSMcs rather than Ecs (41).…”
Section: Discussionmentioning
confidence: 54%
“…Immunohistochemistry analysis was done as previously reported by our group . Briefly, after paraffin‐embedded sections were cut at 4‐μm sections, the slides were deparaffinized and transferred through progressive ethanol gradients for rehydration.…”
Section: Methodsmentioning
confidence: 99%
“…Growth factors and cytokines, such as VEGF, insulin-like growth factor (IGF), HGF, interleukin-1b (IL-1b), and IL-6, have been investigated as therapeutic targets in various cell types and diseases. 8,[36][37][38] Recently, these molecules, secreted by MSCs, have been examined in repair and regeneration therapy. 35 We thus investigated the para-crine effect of LEF1/hUCB-MSCs via enhanced secretion of growth factors and cytokines.…”
Section: Lef1 Expression In Hucb-mscs Triggers the Production Of Varimentioning
confidence: 99%